Flowering phases and pollen viability in interspecific hybrid accessions of açai palm (Research, Society and Development, 2023)
Flowering stages and pollen viability were evaluated in interspecific hybrid accessions between E. oleracea Mart. and E. precatoria Mart., and compared with their parents, in order to subsidize the genetic improvement of the açaizeiro. In six plants representing the two hybrids, a newly exposed bract was marked to monitor the duration of the male phase (DFM), duration of the interval or overlap of phases (IEF/SEF), duration of the female phase (DFF), total duration of flowering (DTF), all expressed in days. The in vivo pollen viability was made based on the colorimetric method, using Baker's solution and obtained from 10 representative plants of each hybrid access (H1 and H2), being performed for two stages: flower bud in pre-anthesis (BPA) and newly opened flower (FRA), collected in the morning, between the hours of 9 to 11 hours. The hybrids obtained an average for the male phase of 12.2 days (H1) and 13.2 days (H2) with a variation of 7 to 33 days, while the female phase reached an average of 4.6 days, with a variation of 3 to 8 days. As for (IEF/SEF) the average was 1.8 and 2.7 days in H1 and H2, respectively ranging from -4 to 7 days, with an average of (DTF) in the two hybrids of 19.8 days. The pollen viability rates were satisfactory for the two stages evaluated (> 70%) important in hybridization. The duration of flowering stages in the hybrid accessions is resembled the female parent (E. oleracea), but with floral anomalies.